2020
DOI: 10.5582/ddt.2020.03067
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory diagnosis of COVID-19 in Africa: availability, challenges and implications

Abstract: Africa, challenges, COVID-19, implications, laboratory diagnosisThe COVID-19 infection has been a matter of urgency to tackle around the world today, there exist 200 countries around the world and 54 countries in Africa that the COVID-19 infection cases have been confirmed. This situation prompted us to look into the challenges African laboratories are facing in the diagnosis of novel COVID-19 infection. A limited supply of essential laboratory equipment and test kits are some of the challenges faced in combat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 28 publications
4
14
1
1
Order By: Relevance
“…Various factors have been proposed to explain the overall low numbers of COVID-19 cases and deaths reported from African countries, supporting the assumption that Africa might be less affected by the pandemic. 6 However, our data contradicts this notion, with the overall seroprevalence detected for Omdurman being amongst the highest compared to all compiled studies listed on the SeroTracker from Arora et al 1 Furthermore, considering the high seroprevalences from South Sudan, Cameroon and Mali, [24][25][26] the officially reported case numbers in Africa seem to be highly underreported. For example, a study in Zambia showed a 100 times higher number cases compared to the officially reported cases.…”
Section: Resultscontrasting
confidence: 72%
See 1 more Smart Citation
“…Various factors have been proposed to explain the overall low numbers of COVID-19 cases and deaths reported from African countries, supporting the assumption that Africa might be less affected by the pandemic. 6 However, our data contradicts this notion, with the overall seroprevalence detected for Omdurman being amongst the highest compared to all compiled studies listed on the SeroTracker from Arora et al 1 Furthermore, considering the high seroprevalences from South Sudan, Cameroon and Mali, [24][25][26] the officially reported case numbers in Africa seem to be highly underreported. For example, a study in Zambia showed a 100 times higher number cases compared to the officially reported cases.…”
Section: Resultscontrasting
confidence: 72%
“…Reasons provided to explain this phenomenon; the younger population structure, 4 lower prevalence of cardiovascular diseases 5 and limited capacity for testing. 6 After the first case was declared in Sudan on March 13, 2020, similar data trends were reported. Only 30404 COVID-19 cases were officially recorded up to April 1, 2021, whereof 72% were registered in Khartoum State alone.…”
Section: Introductionsupporting
confidence: 65%
“…However, it is also possible that this clustering may be exaggerated as COVID-19 testing and surveillance systems are potentially limited to urban settings due to scarcity of the testing. 46 Our finding is also notable for clustering of cases in those less than 50 years of age. Though COVID-19-related deaths prominently occur in older people, 47 there is no known age predilection for the infection of the virus.…”
Section: Discussionsupporting
confidence: 52%
“…This experience should act as an impetus for the government of Ethiopia to act in advancing teaching and research laboratories in universities and other research facilities. A lesson of cultivating a culture of collaborative platform with various agencies in good times in the advancement of sciences and medical practice is necessary to lend a hand at times of emergency ( 18 ). Although this is a public health emergency, opportunities have enabled the staff, and students learn new techniques of molecular testing ( 14 ).…”
Section: Discussionmentioning
confidence: 99%